Design Considerations by the Optimisation of PMS Motors - Kollár, B. (Acta Technica Jaurinensis, 2015)
The determination of the targets, the input, implicit and design parameter is very important part in the design optimisation of the permanent magnetic synchronous motors for electric vehicles. We had to define the connections between them, made investigations which assisted to the appropriate optimisation. In this paper the researches for the design optimisation are presented which define the targets correctly and describes the results of the calculations and simulations of the slot fill factor.